MCPro: A Procedural Method for Topologically Correct Isosurface Extraction Based on Marching Cubes - Stahl, Julian; Grosso, Roberto (Proceedings of the International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications, 2025)
In this work, we present an innovative procedural algorithm designed for extracting isosurfaces from scalar data within hexahedral grids. The geometry and the topological features of the intersection of a level set of the trilinear interpolant with the faces and the interior of a reference unit cell are analyzed. Ambiguities are solved without the help of lookup tables, generating a topologically correct triangulation of the level set within the cell that is consistent across cell boundaries. The algorithm is based on constructing and triangulating a polygonal halfedge data structure that includes contours and critical points of the trilinear interpolant. Our algorithm is capable of handling many singular cases that were not solved by previous methods. The efficacy and correctness of the algorithm were tested on a variety of academic and praxis-relevant CT and MRI datasets.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Isosurface Extraction; Marching Cubes; Saddle Points; Topological Correctness; Trilinear Interpolation